Pengembangan Perangkat Pembelajaran Berbasis Proyek Terintegrasi STEM pada Materi Suhu dan Kalor untuk Meningkatkan Keterampilan Generik Sains Dan Kreativitas Peserta Didik: Instrumen Validasi - Rika Ratnasari; Aris Doyan; Muh. Makhrus (Postgraduate, University of Mataram, 2023)
The aim of this research is to develop appropriate (valid and reliable) learning tools to improve students' generic science skills (KGS) and creativity. The tool developed was based on an integrated STEM project on temperature and heat material in terms of the validity and reliability of the instrument. These tools are in the form of syllabus, RPP, LKPD, and teaching materials as well as KGS instruments and creativity instruments. The type of research is Research and Development (R&D). Device development uses the ADDIE model (analysis, design, development, implementation, and evaluation). The research subjects were class XI MIA students at SMAIT Putri Abu Hurairah Mataram. The results of the syllabus validation obtained an Aiken V index score of 0.88 in the very valid category, RPP 0.84 in the very valid category, LKPD 0.81 in the very valid category, teaching materials 0.81 in the very valid category, KGS instruments 0.79 in the valid category, and creativity instrument 0.80 valid category. The overall average validation score is 0.82 with a very valid category. The results of the reliability of the syllabus, RPP, LKPD, teaching materials, KGS instruments and creativity are reliable with an average score of 93%. Based on these results, integrated STEM project-based learning tools are very feasible (valid and reliable) to be used in learning activities to improve students' generic science skills and creativity.